2020
DOI: 10.1007/s00262-020-02767-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of dendritic cells for therapy of B-cell lymphoma with immune checkpoint inhibitors

Abstract: Immune checkpoint blocking (ICB) is a promising new tool of cancer treatment. Yet, the underlying therapeutic mechanisms are not fully understood. Here we investigated the role of dendritic cells (DCs) for the therapeutic effect of ICB in a λ-MYC-transgenic mouse model of endogenously arising B-cell lymphoma. The growth of these tumors can be effectively delayed by antibodies against CTLA-4 and PD-1. Tumor-infiltrating DCs from mice having received therapy showed an upregulation of costimulatory molecules as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Thus, we recently showed that DCs are also functionally modulated and thereby have impact on anti-tumor T-cell responses during ICB. 37 In contrast, macrophages did not show phenotypic or functional changes during ICB treatment in an endogenous tumor model. 12 Further analyses of the complex alterations of the cellular network during therapy with checkpoint inhibitors are warranted.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, we recently showed that DCs are also functionally modulated and thereby have impact on anti-tumor T-cell responses during ICB. 37 In contrast, macrophages did not show phenotypic or functional changes during ICB treatment in an endogenous tumor model. 12 Further analyses of the complex alterations of the cellular network during therapy with checkpoint inhibitors are warranted.…”
Section: Discussionmentioning
confidence: 89%
“…These findings clearly demonstrated that interfering with negative regulators of the immune system either expressed on certain immune cells (i.e., LAG-3) or on tumor cells (i.e., PD-L1) is able to restore an anti-tumor response that induces protective cancer control through the senescence barrier that leads to a stable growth arrest instead of a complete regression. Recent reports further showed the consequences of immune checkpoint blockade (ICB) on other cell types upon treatment in a mouse lymphoma model [126,127]. The antibodies used for ICB had, for instance, favorable effects on immune cells.…”
Section: Induction Of Senescence and Apoptosismentioning
confidence: 99%
“…Moreover, ICB also exerted an influence on DCs: in response to IFNγ produced by T cells and NKs, tumor-infiltrating DCs expressed more co-stimulatory molecules and a higher IL-12/IL-10 ratio. Both effects favored T cell-based immunity, as the DCs showed an improved capability of presentation and the secretion of factors that favor a Th1 cell anti-tumor immune response [127]. Although ICB is generally associated with improved therapeutic effects, and many cancer patients could already benefit from its application, there are still variations in the treatment response that rely on several factors, such as alterations of the TME and the immune system, including the occurrence of immuno-senescence, which is subject of the next section [94,128].…”
Section: Induction Of Senescence and Apoptosismentioning
confidence: 99%
“…The contribution of tumor-associated DCs to anti-PD-L1 therapies was further supported by the fact that patients with renal cell carcinoma or lung cancer treated with PD-L1 blockade (atezolizumab) experienced clinical benefit in the presence of high level of the DC gene signature, thus highlighting the importance of detecting the amount of DCs to support decision-making on treatment option [131]. These recent findings suggest that ICB therapy is effective not only by directly activating T cells, but also by triggering a complex network, in which DCs play a pivotal role at the interface between innate and adaptive antitumor responses [132], and that blocking the PD-1 pathway early with immune checkpoint inhibitors, at the time of priming and expansion of memory T cells, could be critical for enhancing antitumor immunity.…”
Section: Pd-l1 On Dcs and Immune Checkpoint Blockade Therapiesmentioning
confidence: 99%